Candidemia in Febrile Neutropenic Patients; a Brief Report - Yousefi, Maysam; Yadegarynia, Davood; Lotfali, Ensieh; Arab-Mazar, Zahra; Ghajari, Ali; Fatemi, Alireza (Archives of Academic Emergency Medicine, 2018)
Introduction: Febrile neutropenic patients are at risk of serious infections. The aim of the present study is to identify the frequency, species, and susceptibility patterns of candidemia in febrile neutropenic patients. Methods: This cross-sectional study was conducted on febrile neutropenic patients suspected with candidemia who had been referred to 3 educational hospitals during 9 months. Results: The blood samples of 80 febrile neutropenic patients with the mean age of 48§16.6 years were studied (60% female). Five (6.25%) episodes of candidemia were identified. The underlying disease was acute myeloid leukemia in 4 (80%) cases and all 5(100%) cases had central venous catheter and were receiving prophylactic ciprofloxacin and acyclovir. 100% of isolates were found to be susceptible to Voriconazole, 80% to Caspofungin, 60% to Amphotericin B, and 40% to Fluconazole. Conclusion: The frequency of candidemia among the studied febrile neutropenia patients was 6.25%, with 80% mortality rate, and themost frequently identified yeastwas Candida albicans (100% susceptible to Voriconazole).